The Situated Influence of Chronic Pain Perception on Chinese Older Adults’ Self-Management in Home Care - Fang Liu; Min Tong (Geriatrics, 2018)
Background and objective: Worldwide, 26 million older adults die from chronic disease, and chronic pain is typically a part of the experience of chronic disease. This study explores the perception of chronic pain for home-dwelling Chinese older adults and its influence on (1) self-management ability and (2) management and reduction of chronic pain. Methods: Adopting a qualitative study design, we conducted in-depth interviews with 10 Chinese community-dwelling older adults who experience chronic pain. Half of our informants perceive chronic pain, whereas the other half, diagnosed with Alzheimer’s disease, do not report that they perceive chronic pain. Data were analyzed with inductive thematic analysis. Results: Chronic pain perception plays important roles in (1) defining the challenge of self-management, (2) connecting previous caretaking experience, (3) adjusting the identity of self-management, (4) acquiring support from important others and (5) re-planning self-management arrangements. Conclusion: Pain perception helps to motivate Chinese older adults to face health challenges and regain self-management capacity through adjustments in self-identity and care experience with the support of important others. Pain perception can consolidate the situation of independent living of older adults. It helps to motivate Chinese older adults to face health challenges and regain self-management capacity.